Process for Implementing a Quality Management System (QMS) Adapted to Architectural Practices in Tunisia , in the case of ISO 9001 - Zoghlami, Rochdy (My University, 2024)
This article explores the significance of implementing quality management systems (QMS) in  architectural practices, focusing on the ISO 9001 standard and alternative methodologies like  “Planer am Bau.”, the article delves into the benefits and challenges of adopting ISO 9001  and provides insights into setting up a QMS tailored to the unique needs of architectural  firms in Tunisia.
Keywords: ISO 9001; quality management systems; architectural practices